Direct interspecies electron transfer stimulated by coupling of modified anaerobic granular sludge with microbial electrolysis cell for biogas production enhancement. (1st July 2023) - Wei, Yufang; Zhao, Hongbing; Qi, Xuejiao; Yang, Tianxue; Zhang, Junping; Chen, Wangmi; Li, Mingxiao; Xi, Beidou
Graphical abstract: Highlights: Fe-AnGS was prepared by a biologically induced mineralization method. The effect of Fe-AnGS on performance and microbial community was studied. Genes abundance for carbon dioxide reduction pathway increased by 29.40-43.54 %. Inoculation of Fe-AnGS in MEC with glucose improved TMPCE by 11.83–29.30 %. Fe-AnGS inoculation was an efficient strategy to establish and enhance DIET pathway. Abstract: The magnetite nanoparticle-anaerobic granular sludge complex (Fe-AnGS) was formed by a biologically induced mineralization method, then applied in microbial electrolysis cells (MEC) to enhance the direct interspecies electron transfer (DIET) pathway via selective enriched electrogenic microorganisms for biogas production. Results showed with the highest Fe loading amount of 325.03 ± 8.40 mg/gVS, the magnetization and conductivity of Fe-AnGS were improved by 30.94 % and 29.16 %, respectively. The MEC with Fe-AnGS enriched the specific electrogenic microorganisms in the anode and cathode chambers. Simultaneously, genes coding for carbon dioxide reduction [M00567] increased by 29.40–43.54 % and 34.29–43.43 %, respectively. Inoculation of Fe-AnGS in MEC with glucose as substrate enhanced the experimental methane production of the cathode chambers ( EMPC ), and theoretical methane production of the cathode chamber ( TMPCE ) by 8.00–14.10 %, and 11.83–29.30 %, respectively. Consequently, inoculation of Fe-AnGS in MEC could establish and enhance the DIET pathway for methane production.